2017
DOI: 10.1158/1078-0432.ccr-16-1508
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Astrocytic Tumor Progression Potentiated by JAK-mediated Recruitment of Myeloid Cells

Abstract: Purpose While the tumor microenvironment has been known to play an integral role in tumor progression, the function of non-resident bone marrow-derived cells (BMDCs) remains to be determined in neurological tumors. Here we identified the contribution of BMDC recruitment in mediating malignant transformation from low- to high-grade gliomas. Experimental Design We analyzed human blood and tumor samples from patients with low- and high-grade gliomas. A spontaneous platelet derived growth factor (PDGF) murine gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…In addition, we showed that tumor cell spread was significantly reduced especially if slices were pretreated by JAK inhibitor. The reduced number of reactive astrocytes by JAK inhibitor 38 , as well as reduction of tumor growth and increased recruitment of myeloid cell within the tumor was recently investigated 39 . In summary, we reported the immunomodulatory properties of tumor-associated astrocytes within the human glioblastoma environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that tumor cell spread was significantly reduced especially if slices were pretreated by JAK inhibitor. The reduced number of reactive astrocytes by JAK inhibitor 38 , as well as reduction of tumor growth and increased recruitment of myeloid cell within the tumor was recently investigated 39 . In summary, we reported the immunomodulatory properties of tumor-associated astrocytes within the human glioblastoma environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that they act via the expression of the transcription factor STAT3, whereby they produce cytokines to promote a tumor-supportive environment by suppressing the proliferation of anti-tumor CD4 + and CD8 + T cells and promoting the activity of regulatory CD4 + T cells [20]. Interfering with the pro-tumorigenic function of M2 macrophages has been shown to be effective in reducing glioma progression in mouse models and has been proposed as a therapeutic strategy [33, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Various cytokines—but particularly IL-6—are associated with the infiltration of MDSCs in the TME, which are positively correlated with glioma grade and have been shown to exert immune suppressive effects against T and NK cells through expression of enzymes such as arginase that trigger T cell arrest and apoptosis [ 112 , 113 , 114 , 115 , 116 , 117 ]. MDSCs also express IFN-α, which signals through interferon receptor type 1 (IFNAR1) to activate JAK1/STAT1 signaling, thereby upregulating expression of co-inhibitory molecule programmed death ligand-1 (PD-L1) [ 114 ].…”
Section: Biological Principles In Jak/stat Signaling In Glioblastomentioning
confidence: 99%